Supply Chain Decision-Making and Coordination considering Anticipated Regret under Price Discount. (24th July 2020) - Jian, Jie; Li, Huipeng; Zhang, Nian; Su, Jiafu
Abstract : The increasing homogeneous product market has made more competition among companies to focus on improving customers' experience. In order to get more competitive advantages, companies often launch discount products to attract consumers. However, stimulated by discount products, the perception of anticipated regret is becoming stronger, which is an inevitable issue in front of companies with price discount strategy. Considering the impact of anticipated regret for discount products, this paper quantitatively describes the utility functions and deduces the demand functions of original price products and discount products. The theoretical analysis and numerical simulation are used to analyze centralized and decentralized models of supply chain for discount products. On its basis, the revenue-sharing contract is designed to optimize the profits of supply chain. This paper finds that the price of products increases first and then decreases with the increase of regret sensitivity coefficient and consumer heterogeneity. When the regret sensitivity coefficient and consumer heterogeneity are lower, companies in the supply chain can adopt the "skimming pricing" strategy in order to obtain more profits. When the regret sensitivity coefficient and consumer heterogeneity increase, companies in the supply chain can adopt "penetrating pricing" strategies to stimulate market demand. For high regret consumers, manufacturers can adopt a "commitment advertising" strategy to promise price and quality, and retailers can adopt a "prestige pricing" strategy to reduce consumer perception of regret. In response to products with higher differences in consumer acceptance, manufacturers can adopt a "differentiated customization" strategy to meet different types of consumer demand and retailers can adopt a "differential pricing" strategy for precise marketing.